VopE, a Vibrio cholerae Type III Effector, Attenuates the Activation of CWI-MAPK Pathway in Yeast Model System - Bankapalli, Leela K.; Mishra, Rahul C.; Raychaudhuri, Saumya (Frontiers in Cellular and Infection Microbiology, 2017)
VopE, a mitochondrial targeting T3SS effector protein of Vibrio cholerae, perturbs innate immunity by modulating mitochondrial dynamics. In the current study, ectopic expression of VopE was found to be toxic in a yeast model system and toxicity was further aggravated in the presence of various stressors. Interestingly, a VopE variant the lacking predicted mitochondrial targeting sequence (MTS) also exhibited partial lethality in the yeast system. With the aid of yeast genetic tools and different stressors, we have demonstrated that VopE and its derivative VopE∆MTS modulate cell wall integrity (CWI-MAPK) signaling pathway and have identified several critical residues contributing to the lethality of VopE. Furthermore, co-expression of two effectors VopE∆MTS and VopX, interfering with the CWI-MAPK cellular pathway can partially suppress the VopX mediated yeast growth inhibition. Taken together, these results suggest that VopE alters signaling through the CWI-MAPK pathway, and demonstrates the usefulness of yeast model system to gain additional insights on the functionality of VopE.